The Effectiveness of Individualized Education Programs (IEPs) in Promoting Academic Success among Students with Learning Disabilities - Shazia Afzal (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study investigates the effectiveness of Individualized Education Programs (IEPs) in promoting academic success among students with learning disabilities. Drawing from a wide body of literature and evidence-based practices, the research explores how tailored educational plans enhance student engagement, skill development, and achievement. The study evaluates components such as personalized goal-setting, adaptive instructional strategies, and multidisciplinary collaboration. Findings indicate that when effectively implemented, IEPs significantly contribute to academic progress, especially in reading, writing, and mathematics. However, barriers such as lack of teacher training, resource limitations, and poor parental involvement continue to hinder optimal outcomes. The paper concludes with recommendations for policy and practice to improve the implementation of IEPs in inclusive educational settings.